2012
DOI: 10.1245/s10434-012-2543-8
|View full text |Cite
|
Sign up to set email alerts
|

1 or 2 cm Margins of Excision for T2 Melanomas: Do They Impact Recurrence or Survival?

Abstract: In this series, 1 cm margins were associated with a small increase in LR that did not impact OS. This is concordant with the NCCN recommendations; however, a prospective, randomized trial would be optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…23 Several prior studies have shown that widening surgical margins in melanomas between 1mm-4mm in thickness decreases the rate of loco-regional failure, but does not impact survival. 26, 27 Other clinical trials have shown that widening surgical margins does not improve local control of primary invasive melanoma. 2833 All of these studies, however, exclude ALM.…”
Section: Discussionmentioning
confidence: 99%
“…23 Several prior studies have shown that widening surgical margins in melanomas between 1mm-4mm in thickness decreases the rate of loco-regional failure, but does not impact survival. 26, 27 Other clinical trials have shown that widening surgical margins does not improve local control of primary invasive melanoma. 2833 All of these studies, however, exclude ALM.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Balancing cosmesis, function, and morbidity with oncologic outcomes requires careful decision-making with respect to determination of the appropriate margins. 5 Inadequate excision margins increase the risk of local recurrence. 6 Conversely, unnecessarily large margins of excision generate greater morbidity and increased costs.…”
mentioning
confidence: 99%
“…Best discretion refers to the surgeon using a narrow margin to preserve functionality and cosmesis or avoid a potential need for skin graft or flap reconstruction. A more recent single-center, retrospective series directly compared outcomes for a 1 to 2 mm melanoma using a 1 or 2 cm margin width [11]. Hudson et al retrospectively reviewed 576 patients with 224 (38.9%) having a 1 cm margin and 352 (61.1%) having a 2 cm margin width.…”
Section: Introductionmentioning
confidence: 99%